University genres and multisemiotic features: accessing specialized knowledge through disciplinarity - Giovanni Parodi (Fórum Linguístico)
In this article a preliminary description of the Academic PUCV-2010 Corpus is given, in which an account of the reading materials of doctoral students in Biotechnology, Chemistry, Physics, Linguistics, Literature, and History (3,160 texts) is presented. The corpus was collected in twelve PhD programs in six Chilean universities and comprises all the documents students were given to read during their formal curricula, with the exception of those included in the final doctoral research. In the analysis of the 33% of the corpus (1,043 texts), nine multisemiotic artifacts were identified and a quantification of their occurrence across disciplines was determined. Interesting distinctions emerged, based on how in the texts from the six disciplines meanings are constructed. The main empirical findings reveal differences in: a) the number of circulating texts in each discipline and knowledge domain (more empirical sciences versus more theoretical sciences), b) the dominating language in the reading materials (English and Spanish), c) the relationship between discipline and multisemiotic artifacts, c) the predominance of verbal system in Social Sciences and Humanities texts over the mathematic, graphic and typographic in Basic Sciences texts.